Effects of Lippia sidoides essential oil, thymol, p-cymene, myrcene and caryophyllene on rat sciatic nerve excitability - Barbosa,R. (2017)
Lippia sidoides Cham is a typical herb species of Northeast Brazil with widespread use in folk medicine. The major constituents of the essential oil of L. sidoides (EOLs) are thymol, p-cymene, myrcene, and caryophyllene. Several studies have shown that the EOLs and its constituents have pharmacological effects, including antibacterial, anti-inflammatory, antioxidant and neuroprotective activity. Therefore, this work aimed to investigate the effects of the EOLs and their main constituents on rat sciatic nerve excitability. The sciatic nerves of adult Wistar rats were dissected and mounted in a moist chamber. Nerves were stimulated by square wave pulses, with an amplitude of 40 V, duration of 100 μs to 0.2 Hz. Both EOLs and thymol inhibited compound action potential (CAP) in a concentration-dependent manner. Half maximal inhibitory concentration for CAP peak-to-peak amplitude blockade were 67.85 and 40 µg/mL for EOLs and thymol, respectively. CAP peak-to-peak amplitude was significantly reduced by concentrations ≥60 µg/mL for EOLs and ≥30 µg/mL for thymol. EOLs and thymol in the concentration of 60 µg/mL significantly increased chronaxie and rheobase. The conduction velocities of 1st and 2nd CAP components were also concentration-dependently reduced by EOLs and thymol in the range of 30-100 µg/mL. Differently from EOLs and thymol, p-cymene, myrcene and caryophyllene did not reduce CAP in the higher concentrations of 10 mM. These data demonstrated that EOLs and thymol inhibited neuronal excitability and were promising agents for the development of new drugs for therapeutic use.